Effect of coffee on blood pressure and electrocardiographic changes in nicotine users - Kumar, Pradeep; Verma, Dileep Kumar; Narayan, Jagdish; Kanawjia, Preeti; Ghildiyal, Archna (Asian Journal of Medical Sciences, 2014)
Objectives: The objectives of this study were to see the effect of coffee on Heart rate Blood pressure and ECG changes in nicotine users. Methods: The study was conducted on 120 volunteers aged 21-40 years and with body mass index (BMI) between 17.3-28.0 kg /m2 .The subjects were divided into two groups: Control (n=40) and Study group (n=80). Results: Observation suggests that increment in blood pressure, recorded in study group after coffee ingestion, was lesser than that of control group. We also observed that there were no significant changes in diastolic blood pressure in any group while the mean arterial pressure was higher in both the groups following coffee ingestion. Conclusion: Coffee ingestion decreases the heart rate with no changes in QTc, hence we concluded that less amount of coffee ingestion may not be harmful. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10090 Asian Journal of Medical Sciences Vol.6(3) 2015 46-48